Esophageal and gastric cancer incidence and mortality in alendronate users. - Abrahamsen, B; Pazianas, M; Eiken, P; Russell, R; Eastell, R (2012)
Recent studies have reached conflicting conclusions regarding the risk of esophageal cancer with oral bisphosphonates. Prior studies did not record the number of cancer deaths or endoscopy rates, which could be higher in bisphosphonate users and lead to more cancers being diagnosed at a stage when their esophageal or gastric location could be accurately distinguished. We conducted a register-based, open cohort study using national healthcare data for Denmark. Upper endoscopy frequency, cancer incidence and mortality was examined in 30,606 alendronate users (female, age 50+) and 122,424 matched controls. Primary outcomes were esophageal cancer incidence and death because of esophageal cancer. The analysis showed that alendronate users were more likely to have undergone recent upper endoscopy (4.1 versus 1.7%, p < 0.001). Alendronate users had a lower risk of incident gastric cancer [odds ratio (OR) 0.61; 95% confidence interval (CI): 0.39-0.97) and no increased risk of esophageal cancer (OR 0.71; 95% CI: 0.43-1.19). Risk reductions were greater in users with 10+ prescriptions. The risk of dying of esophageal cancer was significantly reduced in alendronate users after 3 years OR 0.45 (95% CI: 0.22-0.92) but not after 9 years (OR 1.01; 95% CI: 0.52-1.95). An additional comparison with etidronate users revealed no statistically significant difference in outcomes. In conclusion, we found no excess in esophageal cancer deaths or incidence. The early decrease in esophageal cancer rates may relate to the greater use of endoscopy before starting alendronate. Longer term observations also indicated no excess risk of esophageal cancer death and a significantly decreased risk of gastric cancer death.